Vegetative-hydraulic parameters generated by agricultural crops for laminar flows under a semi-arid environment of Pernambuco, Brazil. (November 2019) - Cantalice, J.R.B.; Nunes, E.O.S.; Cavalcante, D.M.; Barbosa, B.; Barros Junior, G.; Guerra, S.M.S.; Rolim Neto, F.C.
Highlights: The shallow flow was affected by proximity to water table due to toeslope position. The CD values obtained by two approaches have not shown differences. The Elephant grass showed the highest values of hydraulic resistance. The Elephant grass was able to reduce the water discharge and interrill erosion. Abstract: The structural parameters of vegetation have an important influence on the resistance imposed to shallow flow under the soil, being important in the control of floods, water erosion and sediment transport in the watersheds. Therefore, in order to obtain the hydraulic characteristics of overland flow, the variables of hydraulic resistance generated by the vegetation to surface flow, and the interrill erosion rates under semi-arid region led to the introduction of agricultural crops, through which shallow flows were generated on elephant grass ( Pennisetum purpureum ), corn ( Zea mays sp.) and in a bare Entisol, placed in a toeslope landscape position. Results showed that the flow regime was slow, laminar and interrill erosion occurred (Re < 500 and Fr < 1). Nevertheless, the hydraulic characteristics of overland flow (Vm, h, q and log f) were probably affected by the proximity to the water table, a hypothesis supported by the obtained values for the infiltration. However, corn and principally elephant grass showed high hydraulic resistance to superficial flow and interrill erosion conferred by the highest ground coverage (lowest Ci = 0.198), by the effect of the sub-factors CiI, CiII and CiIII, and the lowest values of sediment concentration (CS), runoff coefficient (C), interrill detachment rate (Di), and soil loss (SL). Our results support the purpose of introducing agricultural crops in the Brazilian semi-arid region since increasing resistance to interrill erosion can be provided. Elephant grass is a more appropriate crop to be inserted under land management protocols in the semi-arid environment.